2022
DOI: 10.3390/s22124487
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Vapochromic Dyes Having Sensing Properties for Vapor Phase of Organic Solvents Used in Semiconductor Manufacturing Processes and Their Application to Textile-Based Sensors

Abstract: Two vapochromic dyes (DMx and DM) were synthesized to be used for textile-based sensors detecting the vapor phase of organic solvents. They were designed to show sensitive color change properties at a low concentration of vapors at room temperature. They were applied to cotton fabrics as a substrate of the textile-based sensors to examine their sensing properties for nine organic solvents frequently used in semiconductor manufacturing processes, such as trichloroethylene, dimethylacetamide, iso-propanol, metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These systems enable an accurate and rapid qualification and quantification of VOCs through the interactions that occur on the surface of the sensor when they experience contact with the analyte [ 30 , 31 ]. Due to their flexibility and scientifically relevant results, sensor array-based systems have proved their suitability for the assessment of common VOCs such as acetone [ 32 ], ethanol [ 33 ], butanol [ 34 ], formaldehyde [ 35 ], triethylamine [ 36 ], methanol [ 37 ], isopropanol [ 38 ], ethyl acetate [ 39 ], benzene [ 40 ], or acetic acid [ 41 ], among many others.…”
Section: Introductionmentioning
confidence: 99%
“…These systems enable an accurate and rapid qualification and quantification of VOCs through the interactions that occur on the surface of the sensor when they experience contact with the analyte [ 30 , 31 ]. Due to their flexibility and scientifically relevant results, sensor array-based systems have proved their suitability for the assessment of common VOCs such as acetone [ 32 ], ethanol [ 33 ], butanol [ 34 ], formaldehyde [ 35 ], triethylamine [ 36 ], methanol [ 37 ], isopropanol [ 38 ], ethyl acetate [ 39 ], benzene [ 40 ], or acetic acid [ 41 ], among many others.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in automated processes, there has been a recent emergence of the need for real-time automatic solubility measurements. For example, in the semiconductor manufacturing process, it is necessary to determine whether the solute in the organic solvent has dissolved [ 7 , 8 ]. Currently, this measurement process is visually verified by humans and is not fully automated.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, numerous researchers have developed organic fluorescence reagents equipped with mechanochromism and vapochromism. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Recently, we reported that N,N 0 -dipyrid-3-yl-1,4,5,8-naphthalenediimide (NDI) linked to two tris(pentafluorophenyl)borane (TPFB) (1) and N,N 0 -bis(2-aminobenzophenone)-1,4,5,8-naphthalenetetracarboxylic diimide (2) formed 2:1 and 1 : 1 complexes, respectively, with toluene as single crystals with fluorescence based on the charge transfer interaction (Fig. 1).…”
mentioning
confidence: 99%